Pengembangan Pembelajaran Penulisan Kreatif Berwawasan Lingkungangan Bidang Bahasa dan Sastra Indonesia bagi Guru dan Siswa Pondok Pesantren Muqimus Sunnah di Palembang - Cahyaningrum Dewojati (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
One of the eﬀorts in supporting Sustainable Development Goals (SDGs) 2030 is noble moraleducation and environmental preservation through learning. In this case, creative writing is seen as an eﬀective learning medium to convey these values. Terefore, the development of environmentally sound creative writing study in the feld of language and Indonesian literature is considered necessary so that this community engagement activity is then implemented in Pondok Pesantren Muqimus Sunnah in Palembang. Te purpose of this community engagement is to improve the creativity of the community in the feld of creative writing that is environmentally sound as an eﬀort to support the Sustainable Development Goals (SDGs). Te method used in this community engagement is by delivering lectures on creative writing and training in both fction and nonfction. Games are also used as ways to covey the workshop materials. From this training, it seems that madrasah teacher and students are very enthusiastic and more eager to write. In conclusion, creative writing training that is embodied in games, as well as criticism of environmental conditions, is necessary to hone the criticality and creativity of the students and teachers in the world of literacy.